Momordica charantia Exosome-Like Nanoparticles Exert Neuroprotective Effects Against Ischemic Brain Injury via Inhibiting Matrix Metalloproteinase 9 and Activating the AKT/GSK3β Signaling Pathway - Cai, Heng; Huang, Lin-Yan; Hong, Rui; Song, Jin-Xiu; Guo, Xin-Jian; Zhou, Wei; Hu, Zhao-Li; Wang, Wan; Wang, Yan-Ling; Shen, Jian-Gang; Qi, Su-Hua (Frontiers in Pharmacology, 2022)
The neuroprotective effect of plant exosome-like nanoparticles (ELNs) remains unknown. In the present study, we isolated and characterized a novel ELNs from Momordica charantia (MC) and investigated the neuroprotective effects against cerebral ischemia-reperfusion injury. In the present study, MC-ELNs were isolated by ultracentrifugation and characterized. Male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) and MC-ELNs injection intravenously. The integrity of blood brain barrier (BBB) was examined by Evans blue staining, and with the expression of matrix metalloproteinase 9 (MMP-9), Claudin-5 and ZO-1. Neuronal apoptosis was evaluated by TUNEL and the expression of apoptotic proteins including Bcl2, Bax and cleaved Caspase 3. The major discoveries include that: (1) Dil-labelled MC-ELNs was identified in infarct area; (2) MC-ELNs treatment significantly ameliorated the BBB disruption, decreased infarct sizes, and reduced neurological deficit scores; (3) MC-ELNs treatment obviously down-regulated the expression of MMP-9 and up-regulated the expression of ZO-1 and Claudin-5. Small RNA sequencing revealed that MC-ELNs derived miRNA5266 reduced MMP-9 expression. Furthermore, MC-ELNs treatment significantly up-regulated AKT/GSK3β signaling pathway and attenuated neuronal apoptosis in HT22 cells. Taken together, these findings indicate that MC-ELNs attenuate ischemia-reperfusion-induced damage to the BBB, and inhibit neuronal apoptosis probably via up-regulation of AKT/GSK3β signaling pathway.